Occurrence, sources and impacts of benzotriazoles and bisphenols in water bodies within protected areas: Killarney National Park, Ireland - Martyna Grzegorzek; Joanna Struk-Sokołowska; Urszula Kotowska; Agnieszka I. Olbert; Fausto A. Canales; Bartosz Kaźmierczak (Water Resources and Industry)
Despite their protected status, national parks may serve as receptors for anthropogenic pollutants such as benzotriazoles (BTRs) and bisphenols (BPs), raising concerns about aquatic ecosystem health and public exposure. In this context, this study aims to assess the occurrence of six BTRs and ten BPs across two sampling campaigns (SCs) in the lakes and streams of Killarney National Park (KNP), Ireland, revealing spatial variation across six sampling points (SPs). A Wilcoxon test revealed no statistically significant differences between individual concentrations in the two SCs. This research utilized ultrasound-assisted emulsification-microextraction for analytes isolation and gas chromatography-mass spectrometry for detection (USAEME-GC/MS) to determine BTRs and BPs concentrations in KNP's water bodies. Among the 34.4 % of occurrences above the limit of detection, BPA, 5Cl-BTR, and UV-P were consistently found across all sampling points and campaigns. Two BTRs (1H-BTR, 4Me-BTR) and five BPs (BPC, BPCl2, BPE, BPG, BPM) were below detection levels in both SCs. The maximum concentrations for BTRs reached 1.537 μg/L (5Cl-BTR, SP2, SC2). BPA concentrations peaked at 7.753 μg/L (SP6, SC2), exceeding the EU's predicted no-effect concentration for freshwater (1.5 μg/L) in six instances across the KNP samples. These findings highlight the importance of targeted monitoring and management strategies in protected areas, which align with the EU Water Framework Directive objectives. This preliminary exploration of BTRs and BPs in KNP water bodies could serve as a valuable basis and benchmark for assessing environmental quality in KNP and similar protected areas worldwide.